Femininity and Melanie Klein: The theme of femininity in her first publications - Klipan, Marcos Leandro; Ferreira Abrão, Jorge Luis [UNESP] (FapUNIFESP (SciELO), 2018)
This work intends to understand the theme of femininity in the first publications of Melanie Klein. We start from the idea that the author, even more radically than Freud, reversed the classical logic of the subjective constitution of the Western world: that the phallus/male would be the starting point for sexual differentiation. In this sense, the Kleinian notion of femininity would base his mother's own design that has become prominent in her theorizing plan and therefore the possibility of revisions on the Oedipus complex and the proposition of new concepts.
Feminilidade e melanie klein: O tema da feminilidade em suas primeiras publicações
Keywords: Feminity; Melanie Klein; Psychoanalysis